Lack of association between Toxoplasma gondii infection and hypertensive disorders in pregnancy: a case–control study in a Northern Mexican population - Cosme Alvarado-Esquivel; Fernando Vázquez-Alaníz; Ada A Sandoval-Carrillo; José M Salas-Pacheco; Jesús Hernández-Tinoco; Luis Francisco Sánchez-Anguiano; Oliver Liesenfeld (Parasites & Vectors, 2014)
Abstract Background The outcome of pregnancy is often threatened by hypertension disorders, i.e. eclampsia. Rate of infection with the protozoan parasite Toxoplasma gondii can be as high as 80% in pregnant women, and infection acquired during pregnancy can lead to fetal death. Very little is known about a potential association between infections, i.e. those with Toxoplasma gondii, and hypertensive disorders during pregnancy. Methods Through a case–control study design, we investigated the presence of anti-Toxoplasma IgG and anti-Toxoplasma IgM antibodies in 146 pregnant women suffering from hypertensive disorders (cases) and 146 age-matched normotensive pregnant women (controls) attending a public hospital in Durango City, Mexico. Obstetric and blood pressure characteristics from cases and controls were also obtained. Results Seroprevalence of anti-Toxoplasma IgG antibodies and IgG titers did not differ significantly in controls (8/146; 5.5%) and cases (9/146; 6.2%). Anti-Toxoplasma IgM antibodies were found in 2 (1.2%) controls and none of the cases. Seroprevalence of T. gondii in controls (5.5%) was similar to seroprevalences found in patients with mild preeclampsia (4/27: 14.8%), severe preeclampsia (5/95: 5.3%), eclampsia (0/16: 0%) and HELLP syndrome (hemolysis, elevated liver enzymes, and low platelet count) (0/8: 0%) (P = 0.23). Conclusions Our results suggest that latent infection with T. gondii is not associated with hypertensive disorders in pregnant women in Northern Mexico. Further studies with larger sample sizes are needed to elucidate the association of infection with T. gondii with hypertensive disorders in pregnancy.